A proposal to identify the maximal metabolic steady state by muscle oxygenation and VO2max levels in trained cyclists - Vasquez-Bonilla, A. A.; González-Custodio, A.; Timón, R.; Olcina, G. (Sport Sciences for Health, 2023)
Purpose Near-infrared spectroscopy (NIRS) sensors measure muscle oxygen saturation (SmO2) as a performance factor in endurance athletes. The objective of this study is to delimit metabolic thresholds relative to maximal metabolic steady state (MMSS) using SmO2 in cyclists.